ASPEK PERLINDUNGAN HUKUM PENDANAAN DONATUR DAN PENERIMA DONASI MELALUI PLATFORM DONATION BASED CROWDFUNDING (STUDI EMPIRIS DI PT KITA BISA INDONESIA) - Tara Aziza Adelia (Fakultas Hukum Universitas Sebelas Maret, 2023)
This research describes legal issues, especially problems in terms of legal protection of funding of donors and donors who make transactions through a crowdfunding donation platform at Kitabisa.com. This research is an empirical legal research. The purpose of this study was to determine aspects of legal protection in the crowdfunding business, especially donation-based crowdfunding in Indonesia. The author conducted research through interview techniques at PT Kita Bisa Indonesia from the Legal section and the distribution of questionnaires with specifications of having used the Kitabisa.com platform both as Campaigners and Donors. The results of this study indicate that there is still a legal vacuum in regulating donation-based crowdfunding supervision mechanisms in Indonesia. The regulations that have been made are no longer relevant to the current situation and change management of technology infrastructure and digitalization, so it seems that donation-based crowdfunding must be forced to follow the regulations regarding the Collection of Money and Goods and Foundation Laws, but there are no regulations that clearly regulate the collection of online donations in Indonesia. Additionally, the donation- based crowdfunding supervision system overseen by the Ministry of Social Affairs is ineffective because the system is unclear and inefficient. This research also shows that the community still does not understand in detail the system and arrangements regarding donation-based crowdfunding, because the platform is still considered unfamiliar in the eyes of the public. Key Words: Financial Technology; Crowdfunding; Legal Protection